A step-by-step reduction method for preparing nano-copper powder

CN122875739APending Publication Date: 2026-10-09JIANGSU JINGLAN RUIFENG NEW MATERIAL TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611331446.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]为此,本发明所要解决的技术问题在于克服现有技术中粒径分布宽、团聚率高、分散剂配位能力不足、二次氧化和批次一致性等问题,从而提供了分阶段精准控速还原和靶向配位稳定的分步制备体系

Benefits of technology

本发明分散性显著提升,制备得到的纳米铜粉,无明显硬团聚,通过SEM表征可观察到颗粒边缘清晰、单颗粒独立分散的微观形貌;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875739A_ABST
    Figure CN122875739A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of metal materials, in particular to a step-by-step reduction preparation method of nano copper powder. The present application adopts a process architecture of step-by-step reduction and two-stage pH regulation, directly solving the technical problems of uncontrollable nucleation and growth, wide particle size distribution and serious agglomeration in the single-step reduction process; the step-by-step coordination mechanism of ethylenethiourea solves the technical problems of insufficient coordination ability of conventional dispersants and inability to achieve long-term stable dispersion of nano copper powder, and the complexation coordination ability with copper ions can also regulate the particle size distribution to obtain mixed nano copper powder of multiple sizes; the two-stage dispersant supplementing method cooperates with pH to block the oxidation path of newly formed copper particles from the source of the reaction process, solving the problems of poor storage stability and easy oxidation failure of nano copper powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal materials technology, and in particular to a stepwise reduction preparation method for nano-copper powder. Background Technology

[0002] Currently, the mainstream process for preparing nano-copper powder using aqueous chemical reduction generally employs a single-step direct reduction strategy. This method has significant technical shortcomings: First, the reduction rate of copper ions is difficult to control precisely, easily leading to explosive nucleation, resulting in a widened particle size distribution and severe agglomeration of the nano-copper powder. Second, during the reduction process, the newly formed copper nuclei are directly exposed to the aqueous oxygen environment without effective surface protection, making the nano-copper powder easily oxidized to cuprous oxide, resulting in a short product shelf life and poor oxidation resistance. Third, most processes use conventional dispersants such as PVP, which have weak coordination ability and cannot simultaneously achieve particle size uniformity and long-term stability. When the resulting nano-copper powder is used in conductive pastes, it is prone to conductive path defects, failing to meet the application requirements of high-density electronic devices. Some existing technologies attempt to enhance the stabilizing effect through a single strong coordinating agent, but this easily leads to excessive copper ion chelation, resulting in incomplete reduction, making it difficult to achieve a balance between dispersibility, yield, and oxidation resistance.

[0003] US006391087B1 discloses a two-step reduction method for preparing micron-sized copper powder. First, an alkali metal hydroxide is added to an aqueous solution of a copper salt containing divalent copper ions to generate copper oxide. Then, a reducing sugar is slowly added to the reaction system to reduce it to cuprous oxide. Finally, a hydrazine-based reducing agent is added to reduce the cuprous oxide to metallic copper of approximately 5 μm in size. This method effectively slows down the growth rate of copper crystal nuclei because the simultaneous addition of copper salt, reducing agent, and stabilizer in a single reaction system would result in an excessively rapid reduction rate, causing instantaneous supersaturation of copper ions in the solution. This would trigger explosive nucleation, forming numerous tiny crystal nuclei that negatively impact the conductivity of the copper paste.

[0004] Current technologies suffer from several drawbacks: the uncontrollable nucleation and growth of copper ions during single-step reduction leads to a wide particle size distribution and high agglomeration rate in nano-copper powder; the insufficient coordination ability of ordinary dispersants prevents the simultaneous improvement of monodispersity and antioxidant properties of nano-copper powder; and traditional mechanical mixing of copper powders with different particle sizes results in secondary oxidation and batch consistency issues. Summary of the Invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the problems of wide particle size distribution, high agglomeration rate, insufficient coordination ability of dispersant, secondary oxidation and batch consistency in the prior art, thereby providing a stepwise preparation system with precise rate control reduction and stable targeted coordination in stages.

[0006] To address the aforementioned technical problems, this invention provides a stepwise reduction preparation method for nano-copper powder, comprising the following steps: S11: Adjust the pH of the copper salt aqueous solution to 8-13, add the first dispersant and the first reducing agent, heat at 40-50℃ for 1-2 h, and separate the solid and liquid to obtain cuprous oxide; S12: Add the cuprous oxide to water, adjust the pH to 3-7, add the second dispersant and the second reducing agent, heat at 70-90℃ for 0.5-1 h to obtain a crude mixture of nano copper powder; S13: Separate the solid and liquid components of the crude nano-copper powder mixture to obtain nano-copper powder.

[0007] Preferably, in steps S11 and S12, the first dispersant and the second dispersant are independently selected from at least one of thiourea, ethylene thiourea (ETU), 1,3-dimethylthiourea and 1,3-diethyl-2-thiourea and their derivatives.

[0008] Further, in steps S11 and S12, both the first dispersant and the second dispersant are selected from ethylene thiourea (ETU). This invention uses ethylene thiourea as the core dispersing and stabilizing component, which is precisely added in both reduction stages. In the first step, the thiourea groups of ETU react with Cu... 2+ The formation of stable five-element chelates slows down the reduction kinetics. In the second step, ETU selectively adsorbs onto the highly active surface sites of newly formed copper particles, forming a dense organic coating layer. This dual action simultaneously achieves particle size refinement and anti-agglomeration effects.

[0009] Preferably, in steps S11 and S12, the first reducing agent and the second reducing agent are independently selected from at least one of glucose, sodium citrate, ascorbic acid, hydrazine hydrate, hydrogen peroxide, formaldehyde, and acetaldehyde.

[0010] The concentration of the first reducing agent in the copper salt aqueous solution is 50-200 g / L, and the concentration of the second reducing agent in the reducing solution is 10-50 g / L.

[0011] Preferably, in steps S11 and S12, the pH is adjusted by adding at least one of ammonia, sodium hydroxide, sodium bicarbonate, oxalic acid, phosphoric acid, nitric acid, hydrochloric acid, sulfuric acid, ammonium chloride, and sodium acetate.

[0012] Preferably, the concentration of the pH adjuster is 50-150 g / L.

[0013] This invention employs a two-step pH switching-step reduction process architecture. In the first step, copper ions are partially reduced under strongly alkaline conditions (pH 8-13) to generate uniformly sized cuprous intermediates, avoiding explosive nucleation in a single-step system and providing uniform nucleation sites for subsequent growth of copper nanoparticles.

[0014] The second stage involves switching the pH to a weakly acidic to neutral range (pH 3-7), which on the one hand inhibits excessive aggregation of cuprous intermediates, and on the other hand avoids spontaneous oxidation of nano-copper under strong alkaline conditions, thus significantly improving the final antioxidant performance of the product. Furthermore, by generating micron-sized copper seed skeletons and nano-sized copper filler particles in the same reaction system, multi-scale composite copper powder with a pre-defined gradation can be obtained in one step without subsequent additional mixing. This directly solves the pain points of traditional physical mixing, such as easy segregation of gradation, hard agglomeration residue, introduction of many impurities, and poor batch consistency. Ultimately, it yields high-dispersion, high-oxidation-resistant electronic-grade composite copper powder with high tap density, low oxidation rate, and batch stability, which is suitable for the preparation of high-end conductive pastes.

[0015] Preferably, in the copper salt aqueous solution, the copper salt is at least one of copper sulfate, copper nitrate, copper chloride, and copper acetate, and the concentration of the copper salt is 150-350 g / L.

[0016] Preferably, the mass ratio of the copper salt, the first reducing agent, and the first dispersant is 100:(50-100):(0.01-0.1).

[0017] Preferably, the mass ratio of the copper salt, the second reducing agent, and the second dispersant is 100:(5-20):(0.01-0.1).

[0018] Preferably, in step S13, after solid-liquid separation, the solid is washed with water, centrifuged, washed with alcohol, and vacuum dried.

[0019] Furthermore, after solid-liquid separation, the solid is washed twice with water, centrifuged, washed once with ethanol, and then dried in a vacuum drying oven at 50-70℃ for 7-9 hours.

[0020] The present invention also provides a stepwise reduction preparation method for the above-mentioned nano-copper powder to obtain nano-copper powder.

[0021] The present invention also provides a nano-copper paste, which is prepared from the above-mentioned nano-copper powder.

[0022] Preferably, the preparation method of the nano-copper paste is as follows: S21: Mix and dissolve benzotriazole and ethanol, then add the above-mentioned nano copper powder. Disperse and stir at room temperature (25±5℃) using a high-speed mixer, centrifuge, and then vacuum dry to obtain the copper powder component. S22: Hydrogenated bisphenol A epoxy resin, tricyclodecanediethanol epoxy resin, terpineol, and diethylene glycol butyl ether acetate are mixed by stirring to obtain a resin carrier. S23: Mix the resin carrier, the accelerator imidazole adduct, and the dispersant oleic acid, and obtain the resin component by stirring. Premix the resin component and the copper powder component to obtain the coarse slurry. S24: The obtained coarse slurry is dispersed once, then added to a vacuum degassing machine for degassing and secondary dispersion to obtain nano copper slurry.

[0023] Compared with the prior art, the above-described technical solution of the present invention has the following advantages: The present invention significantly improves dispersibility, and the prepared nano-copper powder has no obvious hard agglomeration. SEM characterization shows that the micromorphology of the particles has clear edges and the individual particles are independently dispersed. The present invention significantly enhances the antioxidant properties. Ethylene thiourea forms a dense coordination protective layer on the surface of copper particles, and no obvious oxidation or discoloration occurs after being placed at room temperature for more than 30 days. This invention features a wide range of process adaptability, a flexible process parameter window, and strong compatibility between the two-step pH range. It can be directly integrated with existing industrial production lines for aqueous reduction of nano-copper powder, enabling stable batch production and improved production efficiency without large-scale equipment modifications. Furthermore, it can directly generate micron- and nano-mixed copper powders in the same reaction system, effectively reducing batch deviations and better meeting the needs of high-end conductive paste preparation. Attached Figure Description

[0024] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings.

[0025] Figure 1 This is a scanning electron microscope (SEM) image of cuprous oxide prepared in Example 1; Figure 2 This is a SEM image of the nano-copper powder prepared in Example 1; Figure 3 This is a SEM image of the nano-copper powder prepared in Example 2; Figure 4 The image shows the SEM image of the nano-copper powder prepared in Comparative Example 1. Figure 5 This is a SEM image of cuprous oxide prepared in Comparative Example 2; Figure 6 This is a SEM image of the nano-copper powder prepared in Comparative Example 2. Detailed Implementation

[0026] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0027] Example 1: Preparation of nano-copper powder and nano-copper paste The preparation of nano-copper powder is as follows: (1) Dissolve 100 g of anhydrous copper sulfate in 500 mL of deionized water, add 0.5 g of sodium hydroxide, adjust pH=9, add 0.02 g of ethylene thiourea, and heat to 50℃ to obtain system A.

[0028] (2) Dissolve 80 g of glucose in 500 mL of deionized water and heat to 50 °C to obtain system B.

[0029] (3) Add system B dropwise to system A and stir continuously for 1 h at 50°C to obtain cuprous oxide. Use centrifugation to separate the solid and liquid, pour off the supernatant, and wash with deionized water.

[0030] (4) Disperse cuprous oxide in 800 mL of deionized water, add 1 mL of 5wt% sulfuric acid aqueous solution, adjust pH=6, add 0.05 g of ethylene thiourea, heat to 70℃, slowly add 10 mL of 80wt% hydrazine hydrate aqueous solution, continue heating and stirring for 0.5 h, after the reaction is completed, wash the nano copper powder twice with water, centrifuge at 12000 rpm for 5 min, wash once with ethanol solution, and dry in a vacuum drying oven at 60℃ for 8 h to obtain nano copper powder.

[0031] The preparation of nano-copper paste is as follows: (1) Antioxidant treatment: Mix and dissolve 0.4 g of benzotriazole and 200 g of anhydrous ethanol, then add 200 g of dried nano copper powder from Example 1. Stir at 500 rpm for 30 min at 25°C, then transfer to a centrifuge and centrifuge at 12000 rpm for 5 min. Finally, dry under vacuum at 60°C for later use.

[0032] (2) Preparation of resin base material: Preparation of the mixture of resin and solvent: Weigh hydrogenated bisphenol A epoxy resin (produced by Baling Petrochemical, CYDH300, epoxy equivalent 200 g / eq, resin viscosity ≤4000 mPa·s at 25℃), tricyclodecanediethanol epoxy resin (produced by Daicel Chemical, EX-4000, epoxy equivalent 230-248 g / eq, resin viscosity ≤3600 mPa·s at 25℃), terpineol, and diethylene glycol butyl ether acetate according to the mass ratio of 60:10:10:20. Stir the mixture to make it uniform and obtain the resin carrier.

[0033] (3) Preparation of coarse slurry: The resin carrier, accelerator imidazole adduct PN-23 (CAS: 134091-76-2), and dispersant oleic acid are prepared and mixed in a mass ratio of 70:1:1. The resin components are obtained by stirring at 300 rpm using a high-speed disperser. The above resin components and copper powder components are premixed in a mass ratio of 90:10 to obtain coarse slurry.

[0034] (4) Preparation of copper powder slurry: The obtained coarse slurry was poured into a three-roll mill for primary dispersion. The primary dispersed slurry was then added to a vacuum degassing machine for degassing and secondary dispersion to obtain an antioxidant conductive copper slurry. At the same time, a rotational viscometer (BGD162) was used for testing, and the test temperature was controlled at 25℃±0.5℃. A 23# rotor was selected, and the apparent viscosity was tested at 10 rpm. The sample was stirred at low speed to remove air bubbles and then placed at a constant temperature. Each test was repeated three times and the average value was taken. The viscosity range of the copper slurry was 150-230 Pa·s (25℃). The viscosity of the copper slurry obtained in Example 1 was 180 Pa·s (25℃).

[0035] Example 2: Preparation of nano-copper powder and nano-copper paste Preparation of nano-copper powder: (1) Dissolve 100 g of anhydrous copper sulfate in 500 mL of deionized water, add 0.5 g of sodium hydroxide, adjust pH=9, and heat to 50℃ to obtain system A.

[0036] (2) Dissolve 80 g of glucose in 500 mL of deionized water and heat to 50 °C to obtain system B.

[0037] (3) Add system B dropwise to system A and stir continuously for 1 h at 50°C to obtain cuprous oxide. Use centrifugation to separate the solid and liquid, pour off the supernatant, and wash with deionized water.

[0038] (4) Disperse cuprous oxide in 800 mL of deionized water, add 1 mL of 5wt% sulfuric acid aqueous solution to adjust pH=6, then add 0.05 g of ethylene thiourea, heat to 70℃, slowly add 10 mL of 80wt% hydrazine hydrate aqueous solution, and continue heating and stirring for 0.5 h. After the reaction is complete, wash the nano-copper powder twice with water, centrifuge, wash once with ethanol solution, and dry in a vacuum drying oven at 60℃ for 8 h to obtain nano-copper powder. The SEM image of the copper powder is shown in [image missing]. Figure 3 .

[0039] Preparation of nano-copper paste: The copper paste preparation method is the same as in Example 1, except that the viscosity of the copper paste obtained is 200 Pa·s (25℃).

[0040] Comparative Example 1: This comparative example uses the same method as Example 1 to prepare nano-copper powder, except that ethylene thiourea is not added during the two reduction processes; instead, the same mass of polyvinylpyrrolidone is added. SEM images of the copper powder are shown below. Figure 4 .

[0041] Preparation of nano copper paste: The copper paste preparation method is the same as in Example 1, except that the viscosity of the copper paste obtained is 210 Pa·s (25℃).

[0042] Comparative Example 2: This comparative example uses the same method as Example 1 to prepare nano-copper powder, except that the reduction temperature in the second step is adjusted to 50°C. SEM images of the copper powder are shown below. Figure 5 .

[0043] Preparation of nano-copper paste: The copper paste preparation method is the same as in Example 1, except that the viscosity of the copper paste obtained is 200 Pa·s (25℃).

[0044] Comparative Example 3: This comparative example uses the same method as Example 1 to prepare nano-copper powder, except that the reduction temperature in the second step is adjusted to 90℃. SEM images of the copper powder are shown below. Figure 6 .

[0045] Preparation of nano copper paste: The copper paste preparation method is the same as in Example 1, except that the viscosity of the copper paste obtained is 230 Pa·s (25℃).

[0046] Effect Evaluation 1: 1. The conductive copper pastes obtained in Examples 1 to 2 and Comparative Examples 1 to 3 are screen-printed onto a glass substrate.

[0047] 2. Under a nitrogen atmosphere, the sample was cured at 150°C for 10 min on a hot plate heating stage, and then heated to 700°C for sintering for 30 min. After cooling, the volume resistivity was measured.

[0048] 3. The test results are shown in Table 1. The volume resistivity of the multi-size nano-copper paste prepared in Example 1 under a nitrogen atmosphere is 4.4 × 10⁻⁶. -6 The resistivity of the copper paste is significantly lower than that of other examples, measured in Ω•cm. This is mainly because, during the actual copper paste sintering process, copper powder with a D50 of no more than 0.56 μm has a large specific surface area and high surface energy, promoting the formation of low-temperature sintering necks, accelerating densification, and effectively reducing porosity. Larger copper powder particles with a D99 of 4.55 μm provide a mechanical support framework, preventing sintering collapse and improving paste filling and printing stability. The interaction and uniform distribution of copper powders of different sizes are essential for effectively reducing resistivity.

[0049] Table 1. Volume resistivity of copper pastes prepared using different implementation methods

[0050] Effect Evaluation 2: By using the three-laser diffraction combined with dynamic image synchronous analysis technology of the laser particle size analyzer, copper powder is dispersed in an ethanol system. After signal acquisition, the full-dimensional particle size distribution results of the copper powder can be output.

[0051] Regarding the oxidation and discoloration time of copper powder, the initial color of the copper powder is recorded as reddish-brown. When dark red or small areas turn black, it is determined that the copper powder has oxidized and discolored.

[0052] Figure 1 and Figure 2 These are SEM images of the cuprous oxide and copper nanoparticles prepared in Example 1. Figure 1 It can be seen that the obtained cuprous oxide particles are all spherical and uniformly dispersed. This is because the thiourea group of ETU reacts with Cu. 2+ It forms a stable five-element chelate, which slows down the reduction kinetics.

[0053] from Figure 2 As can be seen from the table, the nano-copper powder prepared in this embodiment has a granular structure, and its particle size distribution data is shown in Table 2: D10=0.24 μm, D50=0.56 μm, D90=0.97 μm, D99=4.55 μm. Among them, the proportion of copper powder with a particle size of less than 1 μm is relatively high, which is more conducive to the solidification and sintering of copper paste. In addition to the granular structure, no other morphologies of the product were found, indicating that the nano-copper powder prepared in this embodiment has high purity and is all of near-spherical structure. This is because the sulfur atom (S) and the deprotonated nitrogen atom (N) in the thiourea molecule act as bidentate ligands and react with Cu. 2+ A stable tetrahedral complex [Cu(SC(NH2)2)4] is formed. 2+ Reduce free Cu 2+ Concentration, slowing down the reduction rate, inhibiting explosive nucleation, avoiding some particle size distribution broadening, while retaining the nucleation of submicron copper powder, also spontaneously formed nano and micron mixed copper powder, avoiding the inhomogeneity and oxidation risk brought about by secondary mixing in the later stage. In addition, the degree of oxidation and discoloration of nano copper powder at room temperature was recorded (Table 3). The mixed nano copper powder of Example 1 can achieve no obvious discoloration for 30 days.

[0054] Table 2. Particle size distribution of nano-copper powder prepared by different implementation methods

[0055] Table 3. Antioxidant time at room temperature of nano-copper powder prepared by different implementation methods

[0056] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A stepwise reduction preparation method for nano-copper powder, characterized in that, Includes the following steps: S11: Adjust the pH of the copper salt aqueous solution to 8-13, add the first dispersant and the first reducing agent, heat at 40-50℃ for 1-2 h, and separate the solid and liquid to obtain cuprous oxide; S12: Add the cuprous oxide to water, adjust the pH to 3-7, add the second dispersant and the second reducing agent, heat at 70-90℃ for 0.5-1 h to obtain a crude mixture of nano copper powder; S13: Separate the solid and liquid components of the crude nano-copper powder mixture to obtain nano-copper powder.

2. The stepwise reduction preparation method of nano-copper powder according to claim 1, characterized in that: In steps S11 and S12, the first dispersant and the second dispersant are independently selected from at least one of thiourea, ethylene thiourea, 1,3-dimethylthiourea and 1,3-diethyl-2-thiourea and their derivatives.

3. The stepwise reduction preparation method for nano-copper powder according to claim 1, characterized in that: In steps S11 and S12, the first reducing agent and the second reducing agent are independently selected from at least one of glucose, sodium citrate, ascorbic acid, hydrazine hydrate, hydrogen peroxide, formaldehyde, and acetaldehyde.

4. The stepwise reduction preparation method of nano-copper powder according to claim 1, characterized in that: In steps S11 and S12, the pH is adjusted by adding at least one of ammonia, sodium hydroxide, sodium bicarbonate, oxalic acid, phosphoric acid, nitric acid, hydrochloric acid, sulfuric acid, ammonium chloride, and sodium acetate.

5. The stepwise reduction preparation method of nano-copper powder according to claim 1, characterized in that: The copper salt in the aqueous solution is at least one of copper sulfate, copper nitrate, copper chloride, and copper acetate, and the concentration of the copper salt is 150-350 g / L.

6. The stepwise reduction preparation method of nano-copper powder according to claim 1, characterized in that: The mass ratio of the copper salt, the first reducing agent, and the first dispersant is 100:(50-100):(0.01-0.1).

7. The stepwise reduction preparation method of nano-copper powder according to claim 1, characterized in that: The mass ratio of the copper salt, the second reducing agent, and the second dispersant is 100:(5-20):(0.01-0.1).

8. The stepwise reduction preparation method of nano-copper powder according to claim 1, characterized in that: In step S13, after solid-liquid separation, the solid is washed with water, centrifuged, washed with alcohol, and vacuum dried.

9. A nano-copper powder prepared by the stepwise reduction preparation method according to any one of claims 1-8.

10. A nano-copper paste, characterized in that: It is prepared from the nano copper powder described in claim 9.

Citation Information

Patent Citations

  • Copper fine powder and method for preparing the same

    US6391087B1